2022
DOI: 10.1029/2022ja030940
|View full text |Cite
|
Sign up to set email alerts
|

First Observations of Equatorial Ionospheric Electric Fields Driven by Storm‐Time Rapidly Recurrent Magnetospheric Substorms

Abstract: Geomagnetic storm ionospheric electrodynamics at the magnetic equator are examined in detail using upgraded, higher time resolution, Jicamarca incoherent scatter radar drift observations, SuperMAG geomagnetic field, and solar wind data to study equatorial ionospheric electric fields during the 8 September 2017 storm main and early recovery phases. We show that during a period of mostly large and southward Interplanetary Magnetic Field (IMF) Bz there were numerous daytime prompt penetration vertical and zonal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 51 publications
3
11
0
Order By: Relevance
“…It is worth noting that at least during the 6 September event, these oscillations occurred when Bz was steadily southward and AU/AL fluctuated, indicating a possible connection to substorm PEF. During the substorm PEF events reported by Fejer and Navarro (2022) for the 8 September period, SGDs were similarly present in our GNSS data (figures not shown). Dinsmore et al (2021) reported a semi-coherent ionospheric pulsing structures (SCIPS) feature in dTEC and the Millstone Hill incoherent scatter radar electron density data.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It is worth noting that at least during the 6 September event, these oscillations occurred when Bz was steadily southward and AU/AL fluctuated, indicating a possible connection to substorm PEF. During the substorm PEF events reported by Fejer and Navarro (2022) for the 8 September period, SGDs were similarly present in our GNSS data (figures not shown). Dinsmore et al (2021) reported a semi-coherent ionospheric pulsing structures (SCIPS) feature in dTEC and the Millstone Hill incoherent scatter radar electron density data.…”
Section: Discussionsupporting
confidence: 78%
“…Here we broadly define PEF as ionospheric electric fields observed at mid‐ and low latitudes that could not be explained by either regular wind‐driven dynamo electric fields or storm‐time disturbance wind dynamo, but appear to be primarily of solar wind‐magnetospheric and geomagnetic disturbance origin. Important PEF sources include the IEF change, solar wind dynamical pressure change‐related shock front arrival (e.g., Huang, 2020a; Kikuchi et al., 2016), substorm (Fejer & Navarro, 2022), and SubAuroral Polarization Stream (Huang, 2020b) which may appear extended equatorward (Foster & Burke, 2002) and be impacted by auroral streamers (Gallardo‐Lacourt et al., 2017). Significant progress has been made in our understanding of the PEF since the 1970s, although some fundamental questions remain highly debatable, for example, what is the physics for the solar wind energy and momentum to be transmitted to the low latitude and equatorial ionosphere (Tu & Song, 2019)?…”
Section: Introductionmentioning
confidence: 99%
“…The zonal drift data provided by Jicamarca radar have excellent potential to address the question about low latitude ionospheric electrodynamic coupling. For example, Fejer and Navarro (2022) investigated the response of the ionospheric electric field during substorms using plasma drift data observed by Jicamarca radar. Previous studies (e.g., Fejer et al., 1985; Kudeki et al., 1981) had found that the Jicamarca F region zonal drifts were westward at daytime and eastward at nighttime, indicating the outward and inward electric field, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Jicamarca incoherent scattering radar locates near the magnetic equator (11.9°S, 76.8°W), and measures the vertical and zonal ion velocity in E‐ and F‐region over the magnetic equator since 1962 (Fejer, 2011; Fejer & Navarro, 2022; Fejer et al., 2005). The detailed measuring of F‐region plasma drift can refer to Woodman (1972).…”
Section: Data Setsmentioning
confidence: 99%
“…The streamer events during case#4 (15 March 2015) occurred during nearly steady southward conditions, and we found that overshielding conditions over equatorial latitudes coincided with the bright equatorward extending streamers. Fejer and Navarro (2022) identified substorms based on the sharp decrease in the SML index and suggested that magnetospheric substorms are the main drivers of prompt penetration electric fields during extended periods (over ∼2 hr) of nearly steady southward IMF Bz. However, our study shows that overshielding conditions can be associated with equatorward extended auroral streamers even under southward IMF‐Bz conditions, and the sharp decrease in the SML index can be associated with such streamers (Yadav et al., 2022).…”
Section: Discussion and Summarymentioning
confidence: 99%